Viroid: A Useful Model for Studying the Basic Principles of Infection and RNA Biology - Ding, B.; Itaya, A.
Viroids are small, circular, noncoding RNAs that currently are known to infect only plants. They also are the smallest self-replicating genetic units known. Without encoding proteins and requirement for helper viruses, these small RNAs contain all the information necessary to mediate intracellular trafficking and localization, replication, systemic trafficking, and pathogenicity. All or most of these functions likely result from direct interactions between distinct viroid RNA structural motifs and their cognate cellular factors. In this review, we discuss current knowledge of these RNA motifs and cellular factors. An emerging theme is that the structural simplicity, functional versatility, and experimental tractability of viroid RNAs make viroid-host interactions an excellent model to investigate the basic principles of infection and further the general mechanisms of RNA-templated replication, intracellular and intercellular RNA trafficking, and RNA-based regulation of gene expression. We anticipate that significant advances in understanding viroid-host interactions will be achieved through multifaceted secondary and tertiary RNA structural analyses in conjunction with genetic, biochemical, cellular, and molecular tools to characterize the RNA motifs and cellular factors associated with the processes leading to systemic infection.
Keywords: NUCLEUS; PHLOEM; RNA SILENCING